The Creation of the Tribunals. Issue 2 (April 2016) - Matheson, Michael J.; Scheffer, David
Abstract : This article offers a U.S. perspective on the creation of the Yugoslav and Rwanda criminal tribunals as each nears its conclusion following more than twenty years of judicial proceedings. During the period in which the tribunals were created, one of us (MJM) was the Acting Legal Adviser or Principal Deputy Legal Adviser of the U.S. Department of State, and the other (DS) was Senior Adviser and Counsel to the U.S. Permanent Representative to the United Nations and was subsequently the first U.S. Ambassador-at-Large for War Crimes Issues. Given the leading role played by the United States in the process of creating the tribunals, we hope that our perspective might help to illuminate the critical issues faced at that time.